The Influence Of Individual Characteristics, Job Characteristics, And Organizational Characteristics On Employee Job Satisfaction At Pt Telkom Regional 1 Sumatera - Saputri, Adinda Desi; Waruwu , Ahmad Aswan; Wahyono , Teguh (Universitas Dehasen Bengkulu, 2026)
This study was designed to explore how personal attributes, job characteristics, and organizational features shape employee job satisfaction at PT Telkom Regional 1 Sumatera. It adopted a descriptive quantitative design rooted in the positivist perspective to clarify relationships among variables objectively. From a population of 227 employees, 69 respondents were selected through probability sampling using a simple random technique, giving all members equal chances. The research relied on quantitative information gathered from primary and secondary sources. Data were collected through field observation, questionnaires, and relevant literature review. The analysis employed multiple linear regression to test partial and simultaneous effects. Results indicate that individual, job, and organizational factors each have a positive and significant influence on job satisfaction. Taken together, they also show meaningful effects. These findings confirm that satisfaction is shaped by internal conditions, task design, and organizational support working together. This evidence offers practical guidance for improving workplace policies.